Current estimates of T cell kinetics in humans. Issue 18 (December 2019) - Macallan, Derek C.; Busch, Robert; Asquith, Becca
Abstract: Stable isotope labeling is a generally applicable method of quantifying cell dynamics. Its advent has opened up the way for the quantitative study of T cells in humans. However, the literature is confusing as estimates vary by orders of magnitude between studies. In this short review we aim to explain the reasons for the discrepancies in estimates, clarify which estimates have been superseded and why and highlight the current best estimates. We focus on stable isotope labeling of T cell subsets in healthy humans. Graphical abstract: Image 1 Highlights: Current best estimates of the proliferation and production of CD4 + and CD8 + T cell subsets. Explanation of why estimates vary between studies and which estimates have been superseded. Discussion of the implications of model choice.